Design and Implementation of a Tourism Website User Interface for Yogyakarta using the Scrum Method - Bahirah, Shabrina Hazrati; Ramadhani, Erika (Sistemasi: Jurnal Sistem Informasi, 2025)
The Radya Kartiyasa Website, a cultural tourism promotion platform under the management of the Kawadenan Radya Kartiyasa unit, was designed and implemented as a medium for promoting cultural tourism with a user interface that emphasizes both aesthetics and local cultural values. The primary objective of developing this website is to provide comprehensive information about tourism destinations within the Keraton area and cultural events organized by the Keraton, while simultaneously enhancing the digital image of the Yogyakarta Palace as a premier cultural tourism destination. The development process adopted the Scrum methodology. This approach facilitated short development cycles, high flexibility, and strong team collaboration, as reflected in the stages of product backlog, sprint planning, sprint execution, daily scrum, sprint review, and retrospective. The outcome of this implementation includes the creation of the homepage, destination index, museum visit promotions, event index, museum gallery, about us page, event detail pages, destination detail pages, and a contact us form page. The contribution of this study lies in integrating a modern development methodology with a culturally inspired interface design, aiming to make the website an effective digital tool for promoting, educating, and preserving the cultural heritage of the Yogyakarta Palace.